A vivência do HIV no contexto de relacionamentos estáveis: interpretação descritiva - Deus, Ana Paula Vieira de (2020)
This interpretative description developed in HIV health service, in the metropolitan region of Goiânia, Goiás. The study aimed at understanding the experience of HIV focus on the diagnostic process and the demands health care in the context of stable relationships. Twenty participants, 17 HIV patients and three partnerships (two HIV negative and one HIV positive). Through thematic analysis, the main aspects described was: the HIV diagnostic process; coping with HIV in the socio-affective and sexual context; preventive and therapeutic practices. The HIV diagnostic process was marked by determining factors for seeking health care, after experiencing symptoms, routine tests and confirmation tests of HIV by the partnership. Before the diagnosis, HIV was perceived as something far from its reality. Participants attributed the possible causes of contamination by the virus, unprotected sex, the sharing of sharp materials, blood transfusions and accidents with biological material. Receiving the diagnosis was described as a lonely path, marked by feelings of denial, suffering and isolation that brought complex therapeutic and social demands to these people's lives, requiring readaptation to activities of daily living, with changes in eating, sexual and sexual habits. the need to adhere to drug therapy. The decision to reveal or omit the diagnosis of the partnership and family members was the first step required to face HIV in the socio-affective and sexual context. The fear of exposure and judgment were the justification for choosing to omit the diagnosis. The majority mentioned changes in sexual behavior in terms of the need to implement preventive methods and living with the fear of transmission and insecurity in the relationship. The factors related to the difficulty to continue sexual life were mainly the lack of knowledge about preventive methods and the lack of communication with health professionals. The experience of therapeutic and preventive methods became crucial to rehabilitation to HIV. Antiretroviral drugs have been described as essential to maintaining the health and quality of life. Nevertheless, many described side effects. It was found that the use of condoms before the diagnosis of HIV was a challenge. Many did not use to rely on stable partnership. Other even when diagnosis of HIV still remained on rejection of condom use. Few participants knew the prophylaxis pre and post-exposure to HIV, among these the two discordant couples. It was found that discovery of HIV brings changes and adjustments necessary to maintain life, being of great responsibility of health services support for this confrontation. Sexuality is still superficially addressed by health professionals and focused mainly on the disease, regardless of the quality of the sexual life of the person living with HIV, as well as risk management against this chronic disease. In living with HIV, the greatest challenge is to deal with prejudice, judgment and stigma that make these people exposed to physical and social vulnerability